Position and Authority of the Constitutional Court as a State Institution - Riyah, Juwai (JUSTICES: Journal of Law, 2024)
The Constitutional Court of the Republic of Indonesia is the highest state institution with the same position as the Supreme Court (MA). Initially, the Constitutional Court was an institution intended only to examine the constitutionality (constitutional review) of a law against the constitution. Because of this, the constitutional court is often referred to as "the guardian of the constitution". The Constitutional Court is a new state institution in the Indonesian constitutional system as a result of changes to the 1945 Constitution of the Republic of Indonesia. The function and role of the Constitutional Court in Indonesia has been institutionalized in Article 24C paragraph (1) of the 1945 Constitution which determines that the Constitutional Court has four constitutional authorities ( constitutionally entrusted powers) and a constitutional obligation. This provision is reaffirmed in Article 10 paragraph (1) letters a to d of Law Number 24 of 20023 concerning the Constitutional Court. The four powers of the Constitutional Court are: 1). Testing laws against the 1945 Constitution, 2). Deciding authority disputes between state institutions whose authority is granted by the 1945 Constitution, 3). Deciding on the dissolution of political parties, 4). Resolving disputes about election results.